POLITIK PENYETERAAN DAYAH DI ACEH - Al Muhajir (Islam Futura, 2015)
The relationship between educational institutions and politics is not merely a mutual relationship influence, but also a functional relationship. Institutions and educational processes play important role in structuring the people political behavior in a country or a region. Dayah as the oldest educational institutions in Aceh, which has played a great role, has ups and downs in its legality. After Tsunami and the Helsinki MoU, dayah "ask the right" to not be regarded anymore as stepchildren of any other educational institutions. Due to the struggling, dayah finally get the Acehnese government legality as an formal institution which is equated with other formal educations, and it alumnus could be accepted in some government and private institutions with some requirements be fulfilled that have been decided by the Acehnese government which is formed through the (BPPDA), The Agency of Dayah Educational Development. Nowadays phenomenon shows that between dayah and the Acehnese government have already have symbiotic mutualism.